Performance Measurement Analysis of Athallah Primary Clinic Using Balanced Scorecard Method Approach - Zibran, Muhamad Haikal; Setiawan, Ade Budi; Melani, Maria Magdalena (Institut Bisnis dan Informatika Kesatuan, 2024)
Performance measurement has always been a benchmark for business success, including the type of health service business at Athallah Pratama Clinic. This study uses quantitative descriptive analysis. The aim of this research is to measure performance at the Klinik Pratama Athallah with the concept of a Balanced Scorecard approach from four perspectives, namely: financial perspective, customer perspective, internal business process perspective and growth and learning perspective. The data analysis method used is comparative analysis, namely by comparing the performance measurements that have been achieved by Klinik Pratama Athallah with the performance measurements that have been achieved using the Balanced Scorecard method approach with the total score. It is hoped that the results of this research will mean that Klinik Pratama Athallah can implement performance measurement using the Balanced Scorecard method approach because the large score can show